Respiratory syncytial virus burden among Ugandan adults aged ≥65 years: A 15-year sentinel surveillance study of prevalence, coinfections, and comorbidities (2010–2025) - Haruna Muwonge; Joyce Namulondo; Levicatus Mugenyi; Joweria Nakaseegu; Bridget Nakamoga; Esther Amwine; Roselyne Akugizibwe; Abdul Ssekandi; Mustafa Ssaka; Hassan Kasujja; Godfrey S. Bbosa; David Odongo; et al. (PLoS ONE, 2026)
Background Respiratory syncytial virus is an important cause of acute respiratory illness in older adults, yet data from sub-Saharan Africa remain scarce. Better understanding of its prevalence, coinfections, seasonal patterns, and risk factors in older populations is essential for strengthening surveillance systems and informing prevention strategies in low-resource settings. Methods We conducted a retrospective cross-sectional study using Uganda’s national influenza-like illness and severe acute respiratory infection sentinel surveillance data from December 2010 to January 2025. Adults aged ≥65 years with real-time-PCR results for respiratory syncytial virus, influenza A and B, and SARS-CoV-2 were included. Descriptive analyses summarized prevalence, clinical characteristics, and temporal trends. Poisson regression with robust variance estimated adjusted prevalence ratios for factors associated with infection and hospitalization. Results Among 545 illness episodes (mean age 73.2 years; 54.1% female), the period prevalence of respiratory syncytial virus across 2010–2025 was 4.8% (95% CI 3.3–6.9), comparable to influenza A (4.2%) and lower than SARS-CoV-2 (6.4%). Most RSV cases were mono-infections (92.3%), with rare respiratory syncytial virus–influenza coinfections (0.4%) and no respiratory syncytial virus–SARS-CoV-2 coinfections. Asthma and pneumonia were independent predictors of infection. Hospitalization was strongly associated with asthma, pneumonia, and heart disease. Activity showed seasonal peaks in March and June, with a marked decline during 2020–2021 and resurgence thereafter. Conclusions RSV is a consistent contributor to medically attended respiratory illness among older Ugandan adults, with prevalence similar to influenza A. Although strong associations with asthma and pneumonia were observed, asthma-related findings are based on few cases and should be considered hypothesis-generating. Seasonal clustering and post-pandemic resurgence support integrating respiratory syncytial virus into routine respiratory surveillance and inform the targeted introduction of preventive interventions, including vaccination, in low- and middle-income settings.